The impact of legal advisor‐issuer cooperation on securitization pricing. Issue 5 (16th September 2021) - Karimov, Nodirbek; Kara, Alper; Downing, Gareth
Abstract: We examine the impact of cooperation between legal advisors and issuers on bank securitization pricing using 6, 624 European ABS tranches issued in the European market over the period of 1998 to 2018. We find that previous cooperation is negatively related to initial yield spreads of ABS. Investors seem to attach value to previous cooperation between issuers and legal advisors and consider such transactions less risky by asking for lower yields. We observe that the magnitude of the past relationships is also of importance. Moreover, previous cooperation becomes more important as the risk of the transaction increases. This is especially noticeable when prime (AAA rated) tranches are compared to non‐prime (non‐AAA rated) tranches. Our results also show that the number of legal advisors in a deal does not matter for investors.